I Dovregubbens Hall. Le sale dei giganti come esempi di pastiche nelle saghe nordiche - Gavilli, Ruben (Annali di Ca’ Foscari: Serie Occidentale)
The aim of this article is to prove the presence of pastiche in the descriptions of the halls and palaces of the giants, which seem to imitate the topos of the drinking courts of the kings in Old Norse literature and Arthurian literature. I will try to identify a satisfactory definition of pastiche, based on the theories of Gérard Genette and Margaret Rose, and I will illustrate the relationship between parody and some of the texts of Old Norse literature. Finally, I will illustrate the parodying passages of Kjalnesinga saga and Egils saga einhenda. Here, the presence of pastiche can in fact be useful for understanding the literary panorama of the late Middle Ages in Iceland.